Impact of cashless payments on economic growth of Malaysia - Thong, Qing Han
The use of cashless payment is spreading rapidly not only among the consumers, but also government agencies. The growth in the usage of cashless payment is mostly driven by the Food and Beverage Industry (F&B) as well as retail transactions. In Malaysia, Touch 'n Go eWallet covers most of the retail merchants and received the support from the government to promote cashless payments among the youths via ePemula Credit. Other than that, more government agencies have started to implement cashless payment method for all government services provided. The Ministry of Finance has announced all government services to be made cashless by 2022. Also, the Melaka National Registration Department (NRD) also implemented cashless transactions across Melaka branches. The aim of this paper is to look at the impact brought by these cashless payment instruments on the economic growth of Malaysia. For this study, a VAR approach is used to examine the short-run dynamics between the cashless payment and economic growth. To explain the impact brought by the cashless payment instruments, Variance Decomposition (VDC) and Impulse Response Function (IRF) are conducted. The results show that credit card usage has explain the growth the most as compared to cheque and e-money. Hence, the cashless payment does have significant effect on the economic growth of Malaysia in _the short run. Keywords: Vector Auto Regressive (VAR), cashless payment, economic growth, Malaysia.